Metal-free, radical 1,6-conjugated addition of cyclic ethers with para-quinone methides (p-QMs) - More, Satish G.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2019)
An efficient method for metal-free C-C bond formation between p-quinone methides (p-QMs) and cyclic ethers via a radical pathway to afford substituted diarylmethanes and triarylmethanes or to effect the -alkylation of the cyclic ethers has been developed. Also, the synthesis of 3,3-disubstituted oxindoles with stereogenic quaternary carbon centers was successfully achieved under mild reaction conditions.

Hypervalent iodine(iii) induced oxidative olefination of benzylamines using Wittig reagents - Ramavath, Vijayalakshmi; Rupanawar, Bapurao D.; More, Satish G.; Bansode, Ajay H.; Suryavanshi, Gurunath (New Journal of Chemistry, 2021)
We have developed hypervalent iodine(iii) induced oxidative olefination of primary and secondary benzylamines using 2C-Wittig reagents, which provides easy access to alpha,beta-unsaturated esters. Mild reaction conditions, good to excellent yields with high (E) selectivity, and a broad substrate scope are the key features of this reaction. We have successfully carried out the gram-scale synthesis of alpha,beta-unsaturated esters.

Metal-free, acid-catalyzed 1,6-conjugate addition of NH-sulfoximines to para-quinone methides: accessing to diarylmethine imino sulfanone - More, Satish G.; Rupanawar, Bapurao D.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
We have reported an efficient and metal-free method for the construction of alpha-diarylmethine imino sulfanone using acid-catalyzed 1,6-conjugate addition of sulfoximines on para-quinine methides (p-QMs). This method showed broad functional group tolerance and a wide range of substrate scope with good to excellent yield. The excellent protocol exhibits mild reaction conditions with high atom economy. The practicability of the present method was supported by a Gram-scale reaction.

Oxidative radical-mediated addition of ethers to quinone imine ketals: an access to hemiaminals - More, Satish G.; Kamble, Rohit B.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2021)
The highly regioselective synthesis of substituted hemiaminal via addition of ethers to quinone imine ketals (QIKs) has been developed under metal-free conditions. In the presence of tetrabutylammonium chloride and potassium persulfate (K2S2O8), QIKs couple efficiently with cyclic and acyclic ethers to give hemiaminals. This strategy offers an easy access to substituted hemiaminal ethers with high functional group tolerance in good to excellent yields.

Lewis acid triggered N-alkylation of sulfoximines through nucleophilic ring-opening of donor-acceptor cyclopropanes: synthesis of gamma-sulfoximino malonic diesters - More, Satish G.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2022)
Scandium triflate (Sc(OTf)(3)) catalyzed, mild, and regioselective ring-opening reaction of donor-acceptor (D-A) cyclopropanes has been developed using sulfoximines for the synthesis of gamma-sulfoximino malonic diesters. This protocol allows the synthesis of different N-alkyl sulfoximines in good to excellent yields (up to 94%) with broad functional group tolerance. In this process, N-H and C-C bonds are cleaved to form new C-N and C-H bonds. The feasibility of this method is supported by a gram-scale reaction and synthetic elaboration of the obtained product.

Metal-free access to hindered N-alkyl sulfoximines via in-situ generated Aza-oxyallyl cations from functionalized alkyl bromide - More, Satish G.; Mane, Kishor D.; Suryavanshi, Gurunath (Asian Journal of Organic Chemistry, 2022)
Herein, we report a catalyst-free and mild synthetic method for the construction of hindered N-alkyl sulfoximines derivative. A wide range of hindered di-alkyl sulfoximines can be readily obtained from the reaction of alpha-bromo-hydroxamates with a variety of sulfoximines, including diaryl, aryl-alkyl, di-alkyl and heteroaryl sulfoximines.
Keywords: alpha-Bromo hydroxamates; Aza-oxyallyl cations; Di-alkyl sulfoximines; metal-free; Sulfoximines

Synthesis of 3 alkyl and 1,3-Bis(alkyl)indolizine amides from a-bromohydroxamates - Mane, Kishor D.; Bagwe, Sagar S.; More, Satish G.; Suryavanshi, Gurunath (Tetrahedron Letters, 2023)
A simple and catalyst-free method has been developed for the synthesis of hindered indolizine amide derivatives from functionalized alkyl bromides. The reaction of a variety of indolizine derivatives with azaoxyallyl cations generated in situ from a-bromoamides afforded a wide range of synthetically important mono- and di-alkylated indolizine amide derivatives in good to excellent yields.@2023 Elsevier Ltd. All rights reserved.
Keywords: a -Bromohydroxamates; Amides; HFIP; Indolizine